The Effect of Duration and Methods of Extraction On The Quality of Gambier (Uncaria gambir Roxb - Agus Sudibyo; Salya Sait; Enny Hawani Loebis (Warta Industri Hasil Pertanian, 1988)
A research on the effect of duration and methods of extraction to the quality of gambier has been conducted. Leaves of gambier from Uncaria gambir Roxb were extracted by steaming and boiling for 5, 10 and 15 minutes, then pressed with hydraulic press in 18.000 kg/cm^2 pressure and dried for 3-4 days. All of the gambier product from these extraction treatment have the same quality but the best quality of gambier could be found by steaming for 5 minutes